Architecture and Research Challenges in Blockchain Based Cloud Computing (International Journal of Innovative Research in Engineering & Management, 2021)
Blockchain technology represents a distributed ledger that  maintains a record of all transactions carried out over a network  and distributes those details among the nodes involved. Bitcoin is  a well-known digital money that is applied using the technology  of blockchain. Instead of using the help of a local server, a cloud  system uses a network of far-flung servers to store, manage, and  analyze data. However, it still faces many challenges including  data security, data management, compliance, and reliability.  Throughout this paper, we've discussed some of the cloud's most  pressing issues and proposed solutions based on blockchain  technology integration. In this article, we describe a brief  assessment of earlier studies that discussed the integration of  blockchain and the cloud. During the study, we also developed a  framework to integrate blockchain with the cloud and to  demonstrate the communication between the two.
Keywords: Blockchain Technology; Cloud Computing; Data Security; Data Management